Perbandingan Konstruksi Perkerasan Lentur Dan Perkerasan Kaku Pada Jalan Gulang-Gulang Dusun Koto Kota Sawah Lunto Sta 0+000 – 0+500 Km - Wiwin Putri Zayu; Gusni Vitri; Hazmal Herman; Rangga Fadel (Jurnal Penelitian Dan Pengkajian Ilmiah Eksakta, 2022)
The results of the flexible pavement analysis on Jalan Gulang-Gulang Dusun Koto, Sawahlunto City are based on Component Analysis Method SKBI-2.3.26.1987 are Surface Course (Laston MS 744) 6 cm thick, Base Course (Batu Broken class A) 20 cm thick, Sub base Course (Sirtu Class A) 25 cm thick, while the rigid pavement "AASHTO 1993 method" is a concrete pavement with a thickness of 30 cm and a thin concrete foundation layer (LC) with a thickness of 10 cm. The analysis uses continuous concrete pavement with reinforcement with a plate thickness of 30 cm using shoulders and using D10-20 cm reinforcement for longitudinal and transverse directions. The dowel is installed with D-36 reinforcement with a length of 45 cm, a distance of 30 cm, while the tie bar is installed with D-16 BJTU-24 threaded steel reinforcement with a length of 30 cm. while the tie bar is installed with D-16 BJTU-24 threaded steel reinforcement with a length of 700 mm and a distance of 75 cm. The cost of rigid pavement construction is Rp. 3,039,054,000, - with skinny concrete (LC) specifications of K-175 kg/cm2 and cement concrete layer of K-250 kg/cm2, flexible pavement is Rp.2,910,136,000. shows that flexible pavement can save costs of Rp.128,918,000. With a percentage of 4.24% of the cost of rigid pavement construction. From the results of the comparison of the cost of flexible pavement construction which is cheaper and saves costs